ANALISIS TINGKAT EFEKTIFITAS PAJAK RESTORAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BERAU - Yudha Nursyam Putera (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
This study aims to find out how the level of effectiveness of restaurant tax and its contribution to Regional Native Income in Berau Regency in 2017 –2021.The data used in this study is quantitative data taken from related agencies, namely the Regional Development Agency of Berau Regency.The method used in this study is a literature study and uses secondary data which is also taken from books, scientific journals, and previous research. The analytical tool used is a formula to find the effectiveness and contribution which is then confirmed against the classification of the criteria.The result of this study is that for the year 2017-219 the effectiveness of Restaurant Tax on Local Native Income has fluctuated, based on the calculation of restaurant tax has an average effectiveness of 202% in 2017-2021 or is in the category of